Cansaço emocional acadêmico : contribuições dos traços de personalidade e dos valores humanos - Albuquerque, Andréa Bezerra de (2023)
This dissertation aimed to verify the pattern of relationships between emotional exhaustion, personality traits and human values. For this, two (2) studies were carried out in article format. Article 1 aimed to gather psychometric evidence of the measure Escala de Cansancio Emocional (ECE) in Brazil, and two (2) studies were carried out. In Study 1, 275 university students from Paraíba (Age = 22.49) participated, who answered the ECE and demographic questions. Exploratory factor analysis suggested a one-dimensional solution with adequate reliability, Cronbach's alpha (α) and McDonald's omega (ω) equal to 0.90. In Study 2, 223 university students from Piauí (Age = 21.65) participated. Confirmatory factor analysis showed adequate indicators (CFI = 0.99; TLI = 0.98; RMSEA = 0.05), with satisfactory reliability (α= 0.88) and (ω = 0.91) and unidimensional structure of the Study 1. In short, the studies provide a short measure of 10 items (SCE), which assess emotional fatigue globally with psychometric evidence for Brazil, which may be useful for researchers interested in the subject and its correlates. Article 2 aimed to test the mediating role of human values in the relationship between personality traits and emotional fatigue in university students. A sample of 350 university students (Mage = 23.81; SD = 6.69) from the Northeast region of Brazil was used, 68.6% of whom were female. Participants answered the Basic Values Questionnaire (QVB), the Big Five Personality Factors Inventory (ICGFP), the Emotional Stress Scale (ECE) and sociodemographic questions. Descriptive statistics, correlations, regressions were performed and a mediation model was tested. The mediation model tested showed that the achievement subfunction did not mediate the relationship between the personality trait neuroticism and emotional fatigue, indicating that people with strong traits of neuroticism tend to be tired. Thus, it is concluded that personality traits and human values contribute to the explanation of emotional fatigue, as well as they can help professionals in designing strategies that favor the development of skills in order to minimize the effects of emotional fatigue.